Visual sociology in the understanding of identity in childhood - Camelo, Adriana (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The present article has as principal object to describe the discoveries made in the systematic review of scientific literature published in academic magazines since 2009 and 2021 in terms of the contributions of visual sociology from a representational understanding of identity in infancy in scholar contexts, around the question “which are the contributions of visual sociology to the representation and identity in research made in scholar contexts?”. For its elaboration, the guidelines of the PRISMA declaration (2020) were followed, enriched by some of the contributions of content analysis exposed by Maurice Duverger (1996). Its analysis and systematization were carried out through the MAXQDA qualitative data analysis software. Consequently, the state of the art is exposed around three fundamental aspects: visual sociology, visual narration, and the representation in the study of children’s identity, and it ends with the contributions of such research in scholar contexts.